Cortico force coherence of the finger and toe with slight rhythmic pressure on force sensors using electroencephalography - Hitoshi Maezawa; Masanori Wakida; Masao Matsuhashi (Scientific Reports)
Abstract We investigated the usefulness of cortico-force coherence (CFC) between electroencephalography (EEG) and force signals for assessing sensorimotor cortex function. Fourteen healthy participants performed slight rhythmical pressing with the right finger and right toe at a self-paced rate of 1–3 Hz under the active condition of CFC using a force sensor and electromyography (EMG). For passive CFC, the experimenter pressed the participant’s right finger at a rate similar to that in the active condition. As control, the conventional corticokinematic coherence (CKC) was recorded for the right finger using an accelerometer (ACC). We also recorded CFC in the active condition by pressing the right toe. In all participants, coherence spectra between the 32-channel EEG signals and force, ACC, and EMG signals showed significant peaks (P < 0.01) at the movement frequency peaks or their harmonics. Finger CFC peak value did not differ among the three conditions (active CFC, passive CFC, and CKC). Finger CFC, force sensor, and EMG values showed no differences. Additionally, finger CFC did not significantly differ from toe CFC. The CFC approach with EEG appears promising and useful for the functional assessment of the sensorimotor cortex, with a clinical advantage of conducting measurements using less force and without obvious kinematics.